Pengembangan Urban Farming Komunal sebagai Strategi Ketahanan Pangan di Kawasan Metropolitan Surabaya (Lokasi: RW 02 Kelurahan Jepara, Kecamatan Bubutan, Kota Surabaya, Jawa Timur) - Shafira Aulia Rosyida Irawan; Anoraga Jatayu; Khanaya Fairuz Shiba; Alyssa Lola Eldiana; Gerriscka Rivandani Putri; Anastasya Fitri Violeta; Indira Ariq Hutomo; M. Aditya Rahman; Alya Shoraya Maharani (Sewagati, 2026)
Densely populated urban areas such as RW 02, Jepara Village, Bubutan District, Surabaya City, face limitations in green open space and high dependence on food from outside the region. These conditions have encouraged the development of urban farming as an effort to strengthen community food security. This community service activity was carried out through a participatory approach in the form of Focus Group Discussions (FGD), training in crop cultivation on limited land, and educational activities for children through the Ruang Inspirasi (RUSA) programme. Urban farming was carried out by utilising yards and narrow spaces using polybags for food crops. This programme demonstrates the effectiveness of utilising non-productive spaces, contributing to the achievement of SDG 2 (Zero Hunger) and SDG 11 (Sustainable Cities), and addressing the negative impacts of urbanisation.